Self-calibrated SERS-LFIA biosensor based on AgNF for in-site and rapid detection of protein kinase biomarker PEAK1 - Wang, Yanling; Gao, Yuan; Ge, Xue; Zhuang, Xiwei; Liu, Jianlei; Zhou, Shaoxiong; Li, Mengnan; Zeng, Chijia; Cui, Feiyun; Zhou, Qin (Biosensors & bioelectronics, 2025)
Dysregulation of pseudopodium-enriched atypical kinase 1 (PEAK1) has been implicated in cancer progression and metastasis, highlighting its significance as a biomarker for disease diagnosis and prognosis. The accurate and sensitive detection of PEAK1 is crucial for understanding cellular signaling pathways and identifying potential biomarkers for multiple diseases. Herein, Ag nanoflower (AgNF) was developed to provide superior Raman signal amplification with an analysis enhancement factor (AEF) of 2.8 × 108. On the basis, we present a novel method utilizing a self-calibrated Surface-Enhanced Raman Scattering-Lateral Flow Immunoassay (SERS-LFIA) biosensor enabling quantitative detection of PEAK1 in biological samples. By combining SERS with LFIA, the biosensor ensures accurate quantification, with a limit of detection (LOD) of 1 fg/mL and a wide linear range of 1 fg/mL ∼ 0.1 μg/mL. The characteristics of the biosensor introduced the SERS signal at C dot of the test strip as a self-calibration unit to correct the SERS signal fluctuations caused by internal and external factors. It was also demonstrated that the specificity and reliability of the biosensor by successfully detecting PEAK1 in complex biological samples, including cell lysates and plasma. In conclusion, our study presents a promising advancement in the field of cancer biomarker detection, offering a highly sensitive, specific, and reliable method for point-of-care testing (POCT) of PEAK1 protein. •A novel AgNF with a high enhancement factor of 2.8 × 108 has been developed.•A self-calibrated SERS-LFIA biosensor was developed to quantitatively detect PEAK1 protein.•The key of the self-calibrated SERS-LFIA biosensor was to use the C dot as a self-calibration unit.•The self-calibrates SERS-LFIA biosensor had a limit of detection of 10−12 mg/mL.•The biosensor demonstrated exceptional performance in the detection of PEAK1 in both plasma and cellular contents.